ResumeXpert: An Intelligent Platform for Ranking and Optimizing Job Applications - Nazmi Syahmi Noor Mohd,; Muhammad Haikhal Mohd. Rapi,; Ammar Aqasyah Abd. Jalil,; Mohd Hanifa, Rafizah (Multidisciplinary Applied Research and Innovation, 2026)
In today’s competitive job market, crafting a compelling resume is essential, particularly for fresh graduates and job seekers with limited experience. ResumeXpert is an AI-powered web-based platform designed to assist users in creating optimized resumes that align closely with job descriptions. The system analyzes uploaded resumes, provides personalized formatting, keyword usage, and skills alignment feedback, and recommends suitable job listings from integrated platforms such as LinkedIn, Glassdoor, and JobStreet. ResumeXpert also features a resume ranking function, enabling recruiters to assess multiple applications efficiently. Developed using the Agile methodology, the system incorporates natural language processing (NLP), machine learning techniques, and modern web technologies. User survey evaluation demonstrated high satisfaction levels in usability, functionality, and overall usefulness. ResumeXpert offers an innovative approach to bridging the gap between job seekers and employers by enhancing resume quality and improving job-matching outcomes.